The Effects of Pre-Existing Antibodies on Live-Attenuated Viral Vaccines - Darren Z. L. Mok (Viruses, 2020)
Live-attenuated vaccines (LAVs) have achieved remarkable successes in controlling virus spread, as well as for other applications such as cancer immunotherapy. However, with rapid increases in international travel, globalization, geographic spread of viral vectors, and widespread use of vaccines, there is an increasing need to consider how pre-exposure to viruses which share similar antigenic regions can impact vaccine efficacy. Pre-existing antibodies, derived from either from maternal–fetal transmission, or by previous infection or vaccination, have been demonstrated to interfere with vaccine immunogenicity of measles, adenovirus, and influenza LAVs. Immune interference of LAVs can be caused by the formation of virus–antibody complexes that neutralize virus infection in antigen-presenting cells, or by the cross-linking of the B-cell receptor with the inhibitory receptor, FcgRIIB. On the other hand, pre-existing antibodies can augment flaviviral LAV efficacy such as that of dengue and yellow fever virus, especially when pre-existing antibodies are present at sub-neutralizing levels. The increased vaccine immunogenicity can be facilitated by antibody-dependent enhancement of virus infection, enhancing virus uptake in antigen-presenting cells, and robust induction of innate immune responses that promote vaccine immunogenicity. This review examines the literature on this topic and examines the circumstances where pre-existing antibodies can inhibit or enhance LAV efficacy. A better knowledge of the underlying mechanisms involved could allow us to better manage immunization in seropositive individuals and even identify possibilities that could allow us to exploit pre-existing antibodies to boost vaccine-induced responses for improved vaccine efficacy.